1982
DOI: 10.1007/bf00215711
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of erythrocytes in the subarachnoid space at spinal nerve exits

Abstract: After intracisternal injection of heparinised autologous blood in cats, spinal nerve exits (SNE) of the subarachnoid space (SAS) were examined by scanning and transmission electron microscopy. Phagocytes, erythrocytes and erythrophages (= macrophages which had phagocytosed red blood cells) were found at SNE. Some lining cells of the SAS had retracted from the adjacent cells and had rounded up. Cells which formed an integral part of the subarachnoid lining cells also had phagocytosed erythrocytes. Debris of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To date, it is controversially discussed if erythrophages and siderophages are exclusively generated in the CSF of patients with subarachnoid bleeding. It has been reported that blood contamination of the CSF as consequence of a previous lumbar puncture might induce the development of siderophages (27). Furthermore, it has been supposed that in some cases erythrophages might develop in vitro in the CSF in the presence of artificial blood contamination being not specific for a subarachnoid bleeding (12).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is controversially discussed if erythrophages and siderophages are exclusively generated in the CSF of patients with subarachnoid bleeding. It has been reported that blood contamination of the CSF as consequence of a previous lumbar puncture might induce the development of siderophages (27). Furthermore, it has been supposed that in some cases erythrophages might develop in vitro in the CSF in the presence of artificial blood contamination being not specific for a subarachnoid bleeding (12).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the unique disease-driving function of hemoglobin post-aSAH was reinforced by a mouse model of prolonged intrathecal exposure to hemoglobin, which recapitulated the behavioral, vascular, cellular, and molecular changes seen after human aSAH. 28 Erythrophagocytes in the blood clot, which ingest decaying red blood cells and detoxify heme 29 and may exit the CNS via spinal nerve roots, 30 develop from CNS-resident meningeal and perivascular macrophages 31 and CSF/blood-derived monocytes, 32 but microglia may also participate in the process 33 if there is parenchymal extension of the hemorrhage. However, erythrophagocytosis is unable to clear large blood clots, especially since the CNS is an immune-privileged site with few resident myeloid cells and highly regulated monocyte influx.…”
Section: Methodsmentioning
confidence: 99%